Circular Economic Model of Waste Bank Based on Technological Innovation: A Comprehensive Bibliometric Insight - Yusuf, Rully; Koestoer, Raldi Hendro; Rahmah, Septia Pristi (Journal of Ecohumanism, 2025)
The circular economy contributes to increasing environmental resilience and the social welfare of society. This study aims is to identify the development of an effective waste bank circular economy model through technological innovation. The method used is bibliometric analysis with VOSviewer software. The research results show that the main challenges faced are lack of infrastructure, public awareness, and inadequate regulations in several countries. However, this research also highlights the enormous opportunities offered by circular economy models, such as the creation of new jobs, reduced dependence on non-renewable resources, and increased global competitiveness.